Assembly of complex viruses exemplified by a halophilic euryarchaeal virus - De Colibus, L; Roine, E; Walter, T; Ilca, S; Wang, X; Wang, N; Roseman, A; Bamford, D; Huiskonen, J; Stuart, D (Nature Research, 2019)
Many of the largest known viruses belong to the PRD1-adeno structural lineage characterised by conserved pseudo-hexameric capsomers composed of three copies of a single major capsid protein (MCP). Here, by high-resolution cryo-EM analysis, we show that a class of archaeal viruses possess hetero-hexameric MCPs which mimic the PRD1-adeno lineage trimer. These hetero-hexamers are built from heterodimers and utilise a jigsaw-puzzle system of pegs and holes, and underlying minor capsid proteins, to assemble the capsid laterally from the 5-fold vertices. At these vertices proteins engage inwards with the internal membrane vesicle whilst 2-fold symmetric horn-like structures protrude outwards. The horns are assembled from repeated globular domains attached to a central spine, presumably facilitating multimeric attachment to the cell receptor. Such viruses may represent precursors of the main PRD1-adeno lineage, similarly engaging cell-receptors via 5-fold spikes and using minor proteins to define particle size.